Gambaran tingkat kenyamanan pengguna gigi tiruan sebagian lepasan pada lansia penderita xerostomia - Andhiny Tiara Hakim; Sharren Teguh (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: As someone gets older, changes in saliva and tooth loss are a few of changes that occur in the oral cavity. Dentures are designed to replace missing teeth and can improve mastication, pronunciation, and aesthetics, as well as maintain tissue health and in the oral cavity. Changes in the composition of saliva occur in the elderly, causing saliva production to malfunction and resulting in complaints of dry mouth or xerostomia.reaching the elderly age, the composition of their saliva changes, causing saliva production to malfunction and resulting in complaints of dry mouth or xerostomia. Xerostomia causes discomfort when wearing dentures and causes pain in edentulous patients who wear dentures, it can interfere with chewing, swallowing, tasting, and speaking. Aim: To analyze and identify the description of removable partial denture users with xerostomia in the elderly. Methods: This type of research is descriptive observational with a cross-sectional approach, and the sample population is the elderly with the criteria of age 60 years and over in a nursing home in the Tangerang area, with a purposive sample technique of up to 160 respondents. Data collection via video call using the Summate Xerostomia Inventory and Geriatric Oral Health Assessment Index questionnaires with online Google Forms. Results: A total of 63 respondents (41.7%) reported a good level of comfort, 65 respondents (43%) reported a moderate level of comfort, and 23 respondents (15.2%) reported a poor level of comfort. Conclusion: The majority of elderly people who have xerostomia and wear removable partial dentures fall into the moderate category, which means they are doing well.